Study of relaxation of a cluster of magnetic particles in magnetic field - Gorobets, Yu.I.; Gorobets, S.V.; Melnichuk, I.A.; Legenkii, Yu.A. (Functional Materials, 2004)
A setup is described intended to study the conversion of a cluster of magnetic particles into a supercluster under magnetic field influence. The technique used makes it possible to study the processes associated with the magnetic particle motion during the supercluster formation, the contribution of the domain wall displacement inside the particles to the measured signal being negligible. The relaxation processes during a Ni supercluster formation in magnetic fields of 0 to 160 Oe strength have been studied. The presence of slight changes in the cluster state in the fields lower than the first critical one has been revealed, where no changes in the cluster geometry have been observed before. The typical relaxation curve shape has been found to depend on the formative field amplitude. The saturation time of the particle redistribution process depends non-monotonously on the field amplitude. The dependence maximum is located between the first and second critical fields.